Relationship between safety culture and safety commitment at Weststar Aviation Services in Kota Baharu - Abd. Latif, Said (2015)
The study was conducted to determine the relationship betIen safety culture and safety commitment as Ill as level of safety culture and safety commitment of employees in Iststar Aviation Services Sdn Bhd (WASSB). This survey was distributed among 200 respondents at WASSB by using Loughbourough university safety climate assessment tool kit (2003) to measure safety culture and safety commitment questionnaire developed by Abd Aziz (2008). 140 valid responses was received, all the results of measurement Ire then analysed statistically using SPSS version 22, with descriptive frequencies on demography, correlations and regression analysis. The findings indicated that the level of safety culture and safety commitment is moderately high. Result also indicate that safety culture and safety commitment was partially mediated by employee commitment. Further suggestions Ire discussed according to the findings to complete the conclusions and recommendations.